History of smoking cessation treatment in Poland – the strengthening role of cytisine as the most effective and safe pharmacotherapy - Zatoński, Witold; Janik-Koncewicz, Kinga; Stępnicka, Zuzanna; Zatońska, Katarzyna; Połtyn-Zaradna, Katarzyna; Herbeć, Aleksandra (Journal of Health Inequalities, 2020)
One of the greatest public health successes in Poland since the 1990s has been a decline in tobacco-related morbidity and mortality, including from lung cancer and cardiovascular disease. The steady decline in smoking cigarettes among adults in Poland during this period was among the most important factors contributing to this success. The key enabling factor in this process was the increasing range and availability of different pharmacotherapy supporting smoking cessation, including nicotine replacement therapy, but especially of the safe and affordable cytisine. The popularity of cytisine has been continuously growing among smokers in Poland. New developments in cytisine-based treatments and research in Poland and abroad can further strengthen global tobacco control efforts. Cytisine requires much greater interest from the medical community and from those responsible for public health in Poland.